Phytochemical analysis and biological activities of Artemisia vulgaris grown in different altitudes of Nepal. Issue 1 (31st December 2023) - Sharma, Khaga Raj; Adhikari, Saroj
ABSTRACT: Herbal medication developed from natural products has antibacterial, antioxidant, and antidiabetic effects on human health. This research aimed at the investigation of the biological activities, estimation of total phenolic and flavonoid content, and Gas Chromatography and Mass Spectrometry (GC-MS) profiling of chemical compounds in Artemisia vulgaris root and leaf grown at three different altitudes of Nepal. The radical scavenging property of the extracts was studied by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay, antidiabetic activity was performed by α-amylase inhibition activity, and the total phenolic and flavonoid content was estimated by Folin–Ciocalteu phenol reagent and aluminium chloride colorimetric methods. The IC50 against the DPPH activity shown by the root extract of A. vulgaris grown in Kathmandu was evaluated to be 67.31 ± 2.80 µg/mL, whereas the lowest activity was shown by the leaf extract of A. vulgaris grown in Chitwan of IC50 149.62 ± 2.40 µg/mL. The α-amylase enzyme inhibition activity shown by the root extract grown in Gorkha was found to be 39.43% as compared to the leaf extract grown in Gorkha of 8.69%. The total phenolic content was found to be maximum in root grown in Kathmandu of 96.30 ± 0.52 mg.GAE/g, whereas the least was found in leaf grown in Chitwan of 26.04 ± 1.66 mg.GAE/g. The flavonoid content was found to be maximum in leaf extracts of A. vulgaris grown in Kathmandu of 71.15 ± 2.07 mg.QE/g, whereas the least was found in leaf grown in Gorkha of 31.54 ± 0.70 mg.QE/g. The essential oils extracted from the A. vulgaris growing in Gorkha (862 m altitude) showed the effective antibacterial property against Klebsiella pneumonia and Acinetobacter baumannii with zone of inhibition (ZOI) 12 and 15 mm, respectively. Similarly, the essential oils of A. vulgaris growing in Chitwan (208 m altitude) showed the ZOI 12 and 11 mm against Klebsiella pneumonia and Acinetobacter baumannii, respectively. The positive control used was ampicillin and polymyxin with ZOI of 22 mm. However, the extracts from plants growing in all these altitudes are found to be inactive against these organisms. From the results of this study, it can be concluded that the biological activities of leaf and root extracts of A. vulgaris increased with an increase in altitudes, and the plants grown in high altitudes are the rich sources of secondary metabolites that play a significant role against infectious diseases and diabetes in human beings.